Effect of titanium addition on the structure, microstructure, and selected mechanical properties of as-cast Zr-25Ta-xTi alloys - Kuroda, Pedro Akira Bazaglia (2021)
Ti alloys are the most used metallic materials in the biomedical field due to their excellent biocompatibility associated with good corrosion resistance in body fluids and relatively low elastic modulus. However, the alloys used in the orthopedic area have an elastic modulus that is 2 to 4 times higher than that of human cortical bone. Searching for new alloys for biomedical applications and with low elastic modulus, zirconium gained prominence due to its attractive properties, especially its biocompatibility. The purpose of this paper is to present novel as-cast alloys of the Zr-25Ta-xTi system and analyze the influence of titanium on the structure, microstructure, microhardness, and elastic modulus of the alloys. The alloys were prepared using an arc-melting furnace. X-ray diffraction measurements and microscopy techniques were used to characterize the crystalline structure and microstructure. From structural and microstructural characterizations, it was observed that titanium acted as an α-stabilizing element since its increase in the precipitation of the orthorhombic α” phase, an intermediate phase from β to α phases, in the alloys. Regarding microhardness measurements, the alloys have higher hardness than pure zirconium due to solid solution hardening that detaches the Zr-25Ta alloy, which has a high hardness value of the precipitation of the ω phase. Among the studied alloys, the Zr-25Ta-25Ti alloy is highlighted, demonstrating the lowest result of modulus of elasticity, which is approximately 2 times higher than the human cortical bone, but many alloys used in the biomedical field, such as pure titanium, have elastic modulus values almost 3 times higher than that of human bone.